Does bone mineral density improve the predictive accuracy of fracture risk assessment?: a prospective cohort study in Northern Denmark - Dhiman, Paula; Andersen, Stig; Vestergaard, Peter; Masud, Tahir; Qureshi, Nadeem (BMJ Publishing Group Ltd, 2018)
Objective: To evaluate the added predictive accuracy of bone mineral density (BMD) to fracture risk assessment.Design Prospective cohort study using data between 01 January 2010 and 31 December 2012.